Nitrogen removal bacterial strains, MSNA-1 and MSD4, with wide ranges of salinity and pH resistances. (August 2020) - Zeng, Xiaoying; Huang, Jinhui Jeanne; Hua, Binbin; Champagne, Pascale
Highlights: MSNA-1 and MSD4 with resistances to high salinity and extreme pH were identified. MSNA-1 and MSD4 could resist salinity range of 0–15% and 0–10%, respectively. MSNA-1 and MSD4 could resist a wide pH range of 3–10 and 5–11, respectively. Removals of NH4 + -N by MSNA-1 were 51.2% at salinity of 10% or 49.2% at pH 4. Removals of TN by MSD4 were 62.4% at salinity of 7% or 72.2% at pH 9. Abstract: Nitrogenous wastewater is difficult to treat using conventional microorganisms in high salinity and acidic/alkaline environments. Two halotolerant bacteria, heterotrophic nitrifying Stenotrophomonas sp. MSNA-1 and aerobic denitrifying Pseudomonas sp. MSD4, were isolated, and the amplification of functional genes provided the evidences of nitrogen removal performance. The results regarding salinity and pH resistance showed that strain MSNA-1 is robust at salinities of 0–15% and pH of 3–10. It can remove 51.2% of NH4 + -N (180 mg/L) at salinity of 10% (pH: 7) and 49.2% of NH4 + -N under pH 4 (salinity: 3%). For strain MSD4, it is robust at salinities of 0–10% and pH of 5–11. It can remove 62.4% of TN (100 mg/L) at salinity of 7% (pH: 7) and 72.2% of TN under pH 9 (salinity: 3%). Their excellent salinity and pH resistances make them promising candidates for treating nitrogenous wastewaters under extreme conditions with low operational cost.